Glutathione: subcellular distribution and membrane transport - Oestreicher, Julian; Morgan, Bruce (Biochemistry and cell biology, 2019)
Glutathione (γ-l-glutamyl-l-cysteinylglycine) is a small tripeptide found at millimolar concentrations in nearly all eukaryotes as well as many prokaryotic cells. Glutathione synthesis is restricted to the cytosol in animals and fungi and to the cytosol and plastids in plants. Nonetheless, glutathione is found in virtually all subcellular compartments. This implies that transporters must exist that facilitate glutathione transport into and out of the various subcellular compartments. Glutathione may also be exported and imported across the plasma membrane in many cells. However, in most cases, the molecular identity of these transporters remains unclear. Whilst glutathione transport is essential for the supply and replenishment of subcellular glutathione pools, recent evidence supports a more active role for glutathione transport in the regulation of subcellular glutathione redox homeostasis. However, our knowledge of glutathione redox homeostasis at the level of specific subcellular compartments remains remarkably limited and the role of glutathione transport remains largely unclear. In this review, we discuss how new tools and techniques have begun to yield insights into subcellular glutathione distribution and glutathione redox homeostasis. In particular, we discuss the known and putative glutathione transporters and examine their contribution to the regulation of subcellular glutathione redox homeostasis.